Methods for Assessing Patient–Clinician Communication about Depression in Primary Care: What You See Depends on How You Look. (19th May 2014) - Henry, Stephen G.; Feng, Bo; Franks, Peter; Bell, Robert A.; Tancredi, Daniel J.; Gottfeld, Dustin; Kravitz, Richard L.
<x xml:space="preserve">Abstract</x> Objective To advance research on depression communication and treatment by comparing assessments of communication about depression from patient report, clinician report, and chart review to assessments from transcripts. Data One hundred sixty‐four primary care visits from seven health care systems (2010–2011). Study Design Presence or absence of discussion about depressive symptoms, treatment recommendations, and follow‐up was measured using patient and clinician postvisit questionnaires, chart review, and coding of audio transcripts. Sensitivity and specificity of indirect measures compared to transcripts were calculated. Principal Findings Patient report was sensitive for mood (83 percent) and sleep (83 percent) but not suicide (55 percent). Patient report was specific for suicide (86 percent) but not for other symptoms (44–75 percent). Clinician report was sensitive for all symptoms (83–98 percent) and specific for sleep, memory, and suicide (80–87 percent), but not for other symptoms (45–48 percent). Chart review was not sensitive for symptoms (50–73 percent), but it was specific for sleep, memory, and suicide (88–96 percent). All indirect measures had low sensitivity for treatment recommendations (patient report: 24–42 percent, clinician report 38–50 percent, chart review 49–67 percent) but high specificity (89–96 percent). For definite follow‐up plans, all three indirect measures were sensitive (82–96 percent) but not specific (40–57 percent). Conclusions Clinician report and chart review generally had the most favorable sensitivity and specificity for measuring discussion of depressive symptoms and treatment recommendations, respectively.